A patient navigator and education program for increasing potential living donors: a comparative observational study. Issue 5 (27th March 2016) - Marlow, Nicole M.; Kazley, Abby S.; Chavin, Kenneth D.; Simpson, Kit N.; Balliet, Wendy; Baliga, Prabhakar K.
Abstract: Background and Objectives: Person‐centered clinical environments may promote living donation for patients with end‐stage renal disease (ESRD). We implemented an observational study design to explore whether a patient navigator (PN) program with person‐centered education in nephrology practice settings could increase potential living donors (PLDs) and, subsequently, increase living transplantation. Design, setting, participants, and measures: Patients referred to (N = 4621) and/or transplanted at (N = 950) our transplant center during 2007–2012 were eligible for inclusion. Two analytical study populations were derived from propensity score matched patient groups. Outcomes comprised total PLDs per candidate and living vs. deceased transplantation for recipients. Results: Multivariable generalized estimating equations logistic regression showed that PN practice candidates were significantly more likely to have an initial inquiry PLD (odds ratio [OR] = 1.21, 95% confidence interval [CI] = 1.01–1.44) and a preliminary screening PLD (OR = 1.27, 95% CI = 1.05–1.54), while there were no significant differences observed in evaluated PLD (OR = 0.94, 95% CI = 0.61–1.45). Conclusions: Our results suggest that our person‐centered PN program stimulated willingness to seek living transplantation and was associated with a trend toward increased LD.